Treatment and rehabilitation of drug dependants and application of the “drug treatment and rehabilitation on act, 1983” / Ahmad Daud - Daud, Ahmad (Faculty of Law, 1983)
This project paper was written to study the developments and cause of drug dependency, its treatment and rehabilitation and the application of the Drug Dependant: (Treatment And Rehabilitation) Act (DDTRA), 1983. in carrying out thn program of treating and rehabilitating known drug dependants either in Governmental or Private Centres is authorised in the Act. From 1970 to 1983. some 93618 person have been identified as drug dependants. The number in 1980 were 7154 new canal, 10391 in 1981, 13563 in 1982 and 14624 in 1983. Up to the time this paper was written the number known to have accumulated from 1970 to 1986 was 121145. Due to the ineffectiveness of treatment and rehabilitation of drug dependants under the Dangerous Drug- Act (DDA) 1952 a new Act, the DDTRA 1983 was enacted in order to guide a more effective and conprehensive treatment and rahabilitation programe. The responsibility initially vested to the Ministry of Social and Welfare Service in 1975 was than taken over by the Ministry of Home Affairs.